KETERLIBATAN ORANG TUA LAKI-LAKI DALAM PENDIDIKAN SEKS ANAK DI KOTA MAKASSAR - Sadriani, Andi; Arifin, Ibrahim (Universitas Negeri Makassar, 2024)
This study aims to explore the involvement of male parents, especially fathers, in children's sex education in Makassar City. This study uses a qualitative approach with a focus on individual experiences in the specific context of father involvement in sex education. A total of 10 fathers domiciled in Makassar City became participants in this study. Data were obtained through in-depth interviews, then analyzed using thematic methods to identify main patterns and themes. The results of the study indicate that: 1) Father involvement in children's sex education is still relatively minimal, although there is awareness and encouragement to be more active in this role; 2) The biggest obstacles faced by fathers are strong cultural and social barriers, where many fathers feel uncomfortable discussing sex with their daughters because they consider the topic too sensitive and taboo; 3) The role of technology and new awareness in the modern era contributes to changes in the way parents educate their children. Some fathers use the internet as a source of information to help them understand how to talk about sex with their children. This study highlights the importance of cultural and social support to encourage father involvement in sex education and the need to utilize technology as a means of supporting parent education.